Estratégias de estimação de canal para adaptação de enlace em sistemas MIMO-OFDM - Moreira, Darlan Cavalcante (2006)
Nowadays the internet is a widely used tool and the great development and popularity of wireless technologies leads us to a future where the connectivity will be characterized as “anywhere, anytime”. Such characteristic is considered essential in 4G systems. However, for a satisfactory user experience a secure and efficient connectivity has to be always available. To obtain such efficiency, the research community has generated a number of promising solutions that achieve significative improvements in system performance, such as adaptive modulation and coding, space-time coding, multiple antennas and MIMO (Multiple Input Multiple Output ) channels, multicarrier modulation, multiuser detection, etc. [1]. Among these solutions, the system adaptation is a particularly interesting one, there is, the system must constantly adapt itself to achieve the best performance for each situation. However, one important premise for the system adaptation is the knowledge of the channel state information (CSI). To obtain this knowledge, several channel estimation strategies were proposed in the literature, each one with advantages and disadvantages. In this work we analyze the impact of channel estimation in the link adaptation through computer simulations1. Two channel estimation techniques with different characteristics were analyzed for some specific scenarios in a MIMO-OFDM (Multiple Input Multiple Output - Orthogonal Frequency Division Multiplexing ) system. To perform the analysis it was used a metric that consider the redundancy introduced to estimate the channel and the channel estimation error of each technique. The obtained results constitute curves that can be used to perform link adaptation in a more realistic way, that is, considering the effect of channel estimation. Besides, it is shown that even the choice of the channel estimation strategy can be an adaptable parameter so that the most adequate channel estimation strategy for each system state is used.